Circular village: o ensino da economia circular na gestão da construção civil - Teodósio, Pamella Menezes (2024)
Sustainability has been gaining ground in discussions across various sectors, presenting itself as a way to reduce environmental problems, and the construction industry is one of them. Therefore, studies are needed to develop ways to carry out construction activities with reduced or scarce degrading actions. As a result, the concept of circular economy has been under discussion. To introduce this topic into the academic environment, both for professionals in training and those already in the workforce, games can be used as a tool for active methodology. Thus, this research aims to construct and apply a didactic game for teaching the theme "Circular Economy in Construction Management". For this purpose, a method based on Design Science Research was developed, including Systematic Literature Mapping, bibliographic research, formulation and application of forms during indirect observation of didactic games for a deeper understanding of learning games, as well as the research of essential elements for the construction of such games, game design, application, and validation of the artifact. The final part of the methodology consisted of describing the developed game, its application, and pre- and post-dynamic questionnaires to observe the learning process for students and teaching for teachers. Regarding the results, the entire DSR process allowed the construction of a didactic game reconciling construction management learning with circular economy, using interlocking building blocks and suitable for training or teaching. Thus, the results indicate that the game contributed to the learning of circular economy topics for students and enabled some teachers to understand the context of circular economy in their discipline, demonstrating its effectiveness as an active methodology tool for teaching. It is hoped that it can be incorporated into the academic context and modified to address new disciplines.